Digitization of monetary transactions in the field of public-private partnership: International-legal experience - Погребняк, Станіслав Петрович; Pohrebniak, Stanislav P.; Панова, Людмила Вячеславівна; Panova, Liudmyla V.; Качурінер, Вікторія Львівна; Kachuriner, Viktoriia L.; Арабаджи, Наталя Борисівна; Arabadzhy, Natalia B. (My University, 2023)
The purpose of the work is to analyze the international legal experience of digitization of monetary payments in the field of public-private partnerships, as well as to highlight key features and positive trends in this matter. The object of the study is the international legal experience of digitization of monetary settlements in the field of public-private partnerships. The research methodology consists of the following research methods: theoretical generalization, scientific abstraction, system analysis, comparative analysis, historical method, and a group of logical methods. With the help of the conducted research, the peculiarities of digitization of monetary settlements in the field of public-private partnerships in different countries were analyzed. In particular, it was determined that the process of digitization of monetary payments in the sphere of public-private partnership differs in different countries.

Teniendo en cuenta que cada vez se digitalizan más esferas de la vida pública, es necesario analizar la digitalización de los pagos monetarios en el ámbito de la colaboración público-privada, teniendo en cuenta la experiencia jurídica internacional. El objetivo del trabajo es analizar la experiencia jurídica internacional de digitalización de pagos monetarios en el ámbito de las asociaciones público-privadas, así como destacar las principales características y tendencias positivas en esta materia. El objeto de estudio es la experiencia jurídica internacional de digitalización de liquidaciones monetarias en el ámbito de las colaboraciones público-privadas. La metodología de investigación consta de los siguientes métodos de investigación: generalización teórica, abstracción científica, análisis de sistemas, análisis comparativo, método histórico y un grupo de métodos lógicos. Con la ayuda de la investigación realizada, se analizaron las peculiaridades de la digitalización de liquidaciones monetarias en el ámbito de las asociaciones público-privadas en diferentes países. En particular, se determinó que el proceso de digitalización de los pagos monetarios en el ámbito de la asociación público-privada difiere en los distintos países.

Мета роботи – проаналізувати міжнародно-правовий досвід цифровізації грошових розрахунків у сфері державно-приватного партнерства, а також виділити ключові особливості та позитивні тенденції у цьому питанні. Об’єктом дослідження є міжнародно-правовий досвід цифровізації грошових розрахунків у сфері державно-приватного партнерства. Методологія дослідження складається з таких методів дослідження: теоретичного узагальнення, наукової абстракції, системного аналізу, порівняльного аналізу, історичного методу та групи логічних методів. За допомогою проведеного дослідження проаналізовано особливості оцифрування грошових розрахунків у сфері державно-приватного партнерства в різних країнах. Зокрема, встановлено, що процес оцифрування грошових розрахунків у сфері державно-приватного партнерства відрізняється в різних країнах.
Digitization of monetary transactions in the field of public-private partnership: International-legal experience / S. P. Pohrebniak, V. P. Liudmyla, V. L. Kachuriner, N. B. Arabadzhy // Revista de la Universidad del Zulia, 3ª época, Año 14, N° 39, 2023.- P. - 432-444. DOI: http://dx.doi.org/10.46925//rdluz.39.24
Keywords: digitization; public-private partnership; monetary policy; contract law; digitalización; sociación público-privada; política monetaria; derecho contractual; державно-приватне партнерство; грошово-кредитна політика; договірне право; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Business and economics; діджиталізація